Optimasi Purifikasi Darbepoetin Alfa Berdasarkan Metode Kromatografi Penukaran ION dengan Dua Variasi Resin: Optimization of Purification of Darbepoetin Alfa Based on ION Exchange Chromatography Method with Two Variations of Resin - Indah Shaliha; Marlia Singgih Wibowo; Neny Nurainit (Jurnal Surya Medika (JSM), 2023)
Kidney failure cases are cases that increase every year. This case cannot be considered trivial because it can threaten someone's life. Indeed, kidney failure is not contagious like other diseases and is caused by a bad lifestyle. The number of cases in Indonesia itself has increased quite sharply. For example, in the Riau Islands the number of dialysis patients experienced a sharp jump from 85 people to 700 people and the increase reached 10 times. Darbepoetin (which is EPO which has more sugar) which is also known as hematopoietic, is a glycoprotein compound that controls the process of erythropoiesis (red blood cell production). This hormone is produced in the kidneys, and some is also produced in the liver. The aim of this research is to purify darbepoetin itself and remove several other proteins or interfering impurities so that darbepoetin itself is ready to be produced and help many people who experience kidney failure. The method used was ion exchange chromatography with Toyopearl DEAE 650 M resin. Optimization was then carried out with various variations, especially the resin variations used were Toyopearl DEAE 650 M and GE-DEAE resins. Based on the results, DPO can be purified with Toyopearl resin. After that, purification optimization was carried out and it was found that TOSOH-DEAE resin was indeed a better resin than GE-DEAE.